2020
DOI: 10.2478/jccm-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Prognostic Impact of Hypernatremia in Sepsis and Septic Shock Patients in The Intensive Care Unit: A Single Centre Experience

Abstract: IntroductionHypernatremia is a commonly associated electrolyte disturbance in sepsis and septic shock patients in the ICU. The objective of this study was to identify the prognostic value of hypernatremia in sepsis and septic shockMaterial and MethodsA prospective study conducted on sepsis and septic shock patients diagnosed prior to admission in the ICU in King Hamad University Hospital, Bahrain from January 1st 2017 to February 28th 2019. Data including age, sex, comorbidities, source of sepsis, sodium level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Sodium_max is an interesting feature in our XGBoost-based model. Hypernatremia can be an independent predictor of poor outcome in septic patients in the ICU, which is similar to some views [ 38 ]. However, another study [ 39 ] showed the risk of death increased by 71.6% when serum sodium was < 129 mmol/L for patients with sepsis.…”
Section: Discussionsupporting
confidence: 87%
“…Sodium_max is an interesting feature in our XGBoost-based model. Hypernatremia can be an independent predictor of poor outcome in septic patients in the ICU, which is similar to some views [ 38 ]. However, another study [ 39 ] showed the risk of death increased by 71.6% when serum sodium was < 129 mmol/L for patients with sepsis.…”
Section: Discussionsupporting
confidence: 87%
“…The exclusion of patients with insufficient renal function or requirement of renal replacement therapy, of course, partially excludes more severely ill patients and therefore influences mortality rates. A prolonged ICU LOS for patients suffering from ICU-acquired hypernatremia as shown in this study is, however, in accordance with recent literature and emphasizes the significance and importance of the observed illness [ 9 , 11 , 12 , 41 ]. Yet, whether hypernatremia, inflammation, catabolism or the combination of all three led to the observed prolonged ICU LOS cannot be determined by the presented results in this study.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast with hyponatremia, baseline hypernatremia has been shown to be directly associated with the diagnosis of sepsis at admission (16). Additionally, patients presenting both hypernatremia and sepsis are known to have a higher mortality rate than those presenting sepsis alone (17).…”
Section: Introductionmentioning
confidence: 99%